Assessment of Silage Quality and In Vitro Digestibility in Alfalfa and Pomegranate Pomace Based Silages - Mutlu, Seda İflazoğlu; Seven, Pınar Tatlı; Aktaş, Numan Yusuf; Çiçek, Miray Sıla; Yoldaşcan, Ahmet Arslan (Afyon Kocatepe Üniversitesi, 2026)
This study evaluated the effects of pomegranate pomace supplementation on silage quality and in vitro digestibility of alfalfa, a forage crop that is challenging to ensile. For this purpose, three groups were formulated: the alfalfa silage group (A) without pomegranate pomace, a mixed group (APP) containing 50% alfalfa and 50% pomegranate pomace, and a pomegranate pomace silage group (PP) without alfalfa. Each group was ensiled in six jars for 45 days. Based on physical characteristics, the silages were classified as ‘satisfactory’ (A) and ‘excellent–good’ (APP and PP). In the APP group, pomegranate pomace supplementation increased the dry matter content (p<0.001) and Flieg score (p<0.001) of alfalfa silage, while significantly reducing ammonia nitrogen (p<0.05) and pH (p<0.05) levels. The crude ash contents of the A, APP, and PP groups were 11.33%, 7.94%, and 4.72%, respectively, while the ether extract contents were 3.58%, 2.74%, and 1.08%. Statistically significant differences were found among the groups in terms of neutral detergent fiber (p<0.001), acid detergent fiber (p<0.001), acid detergent lignin (p<0.01), and crude cellulose (p<0.001) contents. The in vitro dry matter digestibility values of A, APP, and PP silages were determined as 69.79%, 64.23%, and 61.13%, respectively, while in vitro organic matter digestibility values were 66.75%, 59.94%, and 59.77%, respectively. In conclusion, pomegranate pomace supplementation significantly enhanced fermentation characteristics and overall silage quality. These findings suggest that tannin-rich pomegranate pomace could be a promising additive in high-protein forage silages such as alfalfa, and its effects should be further evaluated at different inclusion levels in animal feeding trials.

Bu çalışma, silolanması güç olan yoncaya nar posası ilavesinin silaj kalitesi ve in vitro sindirilebilirlik üzerine etkilerini değerlendirmek amacıyla yürütülmüştür. Bu kapsamda üç grup oluşturulmuştur: nar posası içermeyen yonca silajı grubu (A), %50 yonca + %50 nar posası içeren silaj grubu (APP) ve yalnızca nar posası silajı grubu (PP). Her grup altışar kavanozda 45 gün süreyle silolanmıştır. Fiziksel özelliklere göre yapılan sınıflandırmada A grubu ‘tatmin edici’, APP ve PP grupları ise ‘çok iyi’ kalite olarak belirlenmiştir. APP grubunda nar posası ilavesi, yonca silajının kuru madde içeriğini (p<0.001) ve Flieg skorunu (p<0.001) artırırken, amonyak azotu (p<0.05) ve pH (p<0.05) düzeylerini önemli ölçüde azaltmıştır. A, APP ve PP gruplarının ham kül düzeyleri sırasıyla %11.33, %7.94 ve %4.72; ham yağ düzeyleri ise %3.58, %2.74 ve %1.08 olarak belirlenmiştir. Nötral deterjan lifi (p<0.001), asit deterjan lifi (p<0.001), asit deterjan lignini (p<0.01) ve ham selüloz (p<0.001) içerikleri bakımından gruplar arasında istatistiksel olarak anlamlı farklılıklar tespit edilmiştir. A, APP ve PP gruplarının in vitro kuru madde sindirilebilirlik değerleri sırasıyla %69.79, %64.23 ve %61.13; organik madde sindirilebilirlik değerleri ise %66.75, %59.94 ve %59.77 olarak bulunmuştur. Sonuç olarak, nar posası ilavesi silajın fermantasyon özelliklerini ve genel kalitesini önemli ölçüde iyileştirmiştir. Bu bulgular, tanen açısından zengin nar posasının yüksek proteinli yem bitkilerinden elde edilen silajlarda umut verici bir katkı maddesi olduğunu ve farklı düzeylerde hayvan denemeleriyle daha ayrıntılı olarak değerlendirilmesi gerektiğini ortaya koymaktadır.
Yonca ve Nar Posası Silajlarında Silaj Kalitesinin ve İn Vitro Sindirilebilirliğin Değerlendirilmesi
Keywords: Veterinary Sciences (Other); Veteriner Bilimleri (Diğer)